Study on sustainable development of pharmaceutical health industry under ecological coordination - Fu, Gan; Zhao, Zhao (Frontiers in Public Health, 2023)
The operational risks of pharmaceutical supply chains are uncertain, especially in the post-pandemic era, where public health emergencies pose a greater risk of supply disruptions. How to deal with the risk of supply disruption and take appropriate avoidance measures to reduce the risk of loss has become one of the focus issues of enterprises. Pharmaceutical raw material suppliers, pharmaceutical manufacturers and medical institutions constitute a complete three-tiered supply chain. On the basis of this, a share contract based on buyback proceeds is designed, and a combination contract based on centralized decision and decentralized decision is used to optimize the order volume of pharmaceutical supply chain members. A pharmaceutical supply chain model considering the out-of-stock cost is established, and a corresponding solution is given. Numerical examples are used to verify the validity of the model and algorithm. Sensitivity analysis of buyback prices and order volumes was also performed. The influence of different parameters on model performance is discussed. Sensitivity analysis was significant. The results of the study indicate that there is a "double sourcing" between upstream pharmaceutical raw materials and downstream major suppliers due to supply disruptions, and therefore a supply chain consisting of multiple standby suppliers needs to be established; At the same time, adjusting the contract parameters can optimize the coordination of pharmaceutical supply chain performance, improve the supply motive of backup suppliers, and ensure the profitability of downstream medical institutions.